Factors with impact on magnitude of the placebo response in randomized, controlled, cross-over trials in peripheral neuropathic pain. Issue 12 (December 2020) - Gillving, Mimmi; Demant, Dyveke; Lund, Karen; Holbech, Jakob V.; Otto, Marit; Vase, Lene; Jensen, Troels S.; Bach, Flemming W.; Finnerup, Nanna B.; Sindrup, Søren H.
Abstract : Abstract: The presence and magnitude of placebo responses is important for the outcome in clinical trials of analgesics. This explorative study aimed at identifying patients and trial-specific factors with impact on this response in randomized, controlled, cross-over trials in peripheral neuropathic pain. Data were derived from 7 trials and included observations on pinprick hyperalgesia, allodynia, and pain on repetitive stimulation. The studies were all performed by the same collaboration group in Denmark. Pain was rated daily using numeric 0 to 10 point rating scales (NRS) and placebo response was calculated as the difference in weekly average or median numeric rating scale from baseline to the last week of treatment. A clinically meaningful placebo response was defined as more than 30% reduction of pain on placebo. In 318 individual observations, the response was on average small (0.17 points, range −4.5 to 6). There was no significant impact on size of placebo response of trial-specific factors such as treatment sequence and chance of having placebo treatment in each period or of the patient-specific factors age, sensory signs, and pain symptoms. The findings were similar in patients having placebo in the first treatment period. There was no marked difference between patients with (n = 43) and without (n = 275) a clinically meaningful placebo response with respect to the patient-specific factors including frequency of sensory signs and symptoms. In conclusion, this study on cross-over trials in peripheral neuropathic pain found no robust impact of trial and patient-specific factors on the placebo response. Abstract : In randomized, controlled, clinical trials with cross-over design in peripheral neuropathic pain, there was no impact of pain symptomatology, sensory signs, pain duration, age, and sex on the placebo response.